METABOLISM REBUILDING OF VAGINA TISSUESIN AT WOMEN WITH ATROPHIC COLPITIS IN POSTREPRODUCTIVE PERIOD - O. G. Sarkysjan; E. G. Krivolapova (Медицинский вестник Юга России, 2015)
RETRACTEDPurpose: the analysis of carbohydrate-energetic metabolism of vaginal tissue taken in conjunction with estimation of interrelations between fatty acids composition and effi cacy of Mg2+and Ca2+-dependent ATP-ase working at women with atrophic colpitis in postreproductive period.Materials and methods: it was established the vaginal tissue of 35 women (age of 51 Ѓ} 2,8лет) with signs of light atrophia. Th e comparative group – 35 women (age of 48 Ѓ} 3,6лет) without pathologic urogenital symptoms. It was established the activity of enzymes of carbohydrate and energetic metabolism, the activity of Ca2+, Mg2+-dependent ATP-ase and composition of fatty acids of vaginal tissue.Results: iIt was found the changes of enzymes of carbohydrate and energetic metabolism at atrophic colpitis. In this situation it was found the increasing of polyunsaturated fatty acids. Th is changes combines with increasing activity of Ca2+, Mg2+-dependent ATP-ase.Summary: results of investigation suggest formation of pathogenic chain in atrophic colpitis. Th is chain binds with change of priority direction of diff erent metabolic pathways, aff ection of cell transport systems work that lead to diff erent system changes on cell level which may be connect not only with aff ection of steroidogenesis but also with disturbance in hormone-receptor sending of diff erent signal systems.